Effectiveness of self-instructional Module on prevention of polycystic ovarian syndrome among adolescent girls in selected Nursing College, Chennai. - Pradhan, Trupti Rekha; Sarkar, Manidipa; Deb, Snigdha (Journal of Neonatal Surgery, 2025)
The major problem faced by adolescent girls is menstrual disorders. Polycystic Ovarian Syndrome is a common endocrine disorder in women of any reproductive age (18- 40 years). PCOS elicits a set of symptoms such as irregular menses, heavy menstruation, pelvic pain, excess hair, facial growth, patches of thick, dark, velvety skin and difficulty in pregnancy. The research is about to improve the knowledge regarding the prevention of polycystic ovarian syndrome among adolescent girls at a selected nursing college. The problem statement of the study is to evaluate the effectiveness of a self-instructional module on the prevention of polycystic ovarian syndrome among adolescent girls at a selected nursing college in Chennai. The objective of the study is to assess the pre-test knowledge regarding the prevention of polycystic ovarian syndrome among adolescent girls in a selected nursing college. To assess the post-test knowledge regarding the prevention of polycystic ovarian syndrome among adolescent girls in selected nursing colleges. To compare the pre-test and post-test knowledge regarding the prevention of polycystic ovarian syndrome among adolescent girls in a selected nursing college. To find out the association between post-test knowledge score with their selected demographic variables. The methodology of the present study was conducted at Sathyabama College of Nursing. The sample of this study consists of 30 students in Sathyabama College of Nursing. The purposive sampling technique was used for the sample selection. The tool used for the data collection was a self-administered multiple-choice questionnaire, which consisted of part one, demographic data, and part two, a PCOS semi-structured questionnaire, knowledge about polycystic ovarian syndrome. Descriptive statistics (frequency, percentage) and inferential statistics (chi-square) were used to analyse the data and set hypotheses. It was concluded that the knowledge regarding the prevention of polycystic ovarian syndrome will be conducted among adolescent girls. This will help to identify and prevent PCOS and improve their quality of life. The results showed that 76% of adolescent girls have gained moderate knowledge, and 24% of them have gained adequate knowledge. The present study is to evaluate the knowledge regarding the prevention of polycystic ovarian syndrome among adolescent girls at a selected nursing college in Chennai. Thus, the investigator was done to evaluate the knowledge of PCOS among adolescent girls of each sample